HUBUNGAN PENGETAHUAN DAN KEBUTUHAN PASIEN TERHADAP INFORMASI OBAT DI APOTEK AMANDIT FARMA BANJARMASIN - Ratih Pratiwi Sari; Aditya Maulana Perdana Putra; Ulfah Masran (Jurnal Ilmiah Manuntung, 2018)
The current pharmaceutical service has shifted its orientation from drug oriented to patient oriented with reference to pharmaceutical care. Pharmaceutical service activities are not limited to drug preparation and drug delivery to patients but pharmacy needs to interact or communication with the patient. The purpose of this study was to determine how is the relationship between knowledge and patient needs for drug information at Amandit Farma Pharmacy Banjarmasin. This type of research is descriptive analysis. Sampling was taken on March 9 - April 8, 2018 by giving questionnaires to 250 patients who redeemed the prescription at Amandit Farma Banjarmasin Pharmacy using systematic random sampling method according to exclusion and inclusion criteria. Data analysis using Chi Square 3x3. Based on the results of this study can be known the relationship between knowledge and needs of patients on drug information at Amandit Farma Pharmacy in Banjarmasin is statistically meaningful